Evaluation of the quality of performance of Rajaee Hospital, Tonekabon, Iran, based on Malcolm Baldrige model - mohammad mehdi mardanshahi; Mohammad Sadegh Sohrabinejad; Mohammad Hasan Shakki (Mazandaran University of Medical Sciences, 2016)
Introduction and Purpose: Evaluation of performance quality plays an important role in client satisfaction, especially in hospitals as healthcare providers. Therefore, we aimed to investigate the quality of performance of Rajaee Hospital in Tonekabon, Iran. Methods: This descriptive survey was performed in 225 of the staff of Shahid Rajaee Hospital during 2015. The samples were randomly chosen according to Krejcie and Morgan’s table. Performance quality was evaluated using the standard checklist of Malcolm Baldrige model. To analyze the data, one-sample t-test and Friedman test were run, using SPSS 18. Results: The total score of Shahid Rajaee Hospital in terms of performance quality was above par (616.482 out of 1010). The "standard of results" was in the first rank of Malcolm Baldrige model and "focus on human resources" ranked last in that model. Conclusion: Although the performance quality was above average, shortcoming in terms of factors associated with market and clients accentuates the importance of planning and focusing on improving the factors affecting the quality of performance.